Pelatihan Kepemimpinan Remaja Berbasis Problem Solving: Upaya Menumbuhkan Jiwa Inisiatif Pemuda - Rahmi Wahyuni; Ardina Khoirun Nisa (Karsa : Jurnal Pengabdian Masyarakat, 2025)
Leadership is an essential skill that needs to be instilled from a young age so that the younger generation can play a role as agents of change in society. This community service activity aims to cultivate a spirit of leadership and initiative among teenagers through leadership training based on a problem-solving approach. The method used in this activity is Participatory Action Research (PAR) with a participatory training approach. The activity was conducted in Pagar Gunung Village, Mandailing Natal Regency, involving 35 teenage participants aged 15–20 from various youth organization backgrounds, such as Karang Taruna, Mosque Youth, and the local school student council. The results of the activity show that this training is capable of enhancing three important aspects in adolescents: (1) an increase in understanding of the basic concepts of leadership and the role of youth as agents of change; (2) an improvement in critical and analytical thinking skills in identifying and seeking solutions to social problems in their environment; and (3) an increase in courage and initiative in voicing ideas and taking an active role in the community. Through pre-test and post-test evaluations, an average increase of 42% in the understanding of leadership concepts was observed. Some participants even committed to implementing solutions to the issues raised in the training, such as waste management, youth literacy activities, and anti-bullying campaigns. This activity not only provides conceptual knowledge but also fosters critical thinking and initiative among the youth. In the future, such programs need to be continued and synergized with educational institutions, youth organizations, and village governments so that their sustainability and social impact become broader and more tangible.